A clinically relevant rodent model of the HIV antiretroviral drug stavudine induced painful peripheral neuropathy - Huang, W; Calvo, M; Karu, K; Olausen, H; Bathgate, G; Okuse, K; Bennett, D; Rice, A (2013)
HIV-associated sensory neuropathy is the most frequent manifestation of HIV disease, afflicting 40-50% of patients whose HIV disease is otherwise controlled by antiretroviral therapy. It often presents with significant neuropathic pain and is consistently associated with previous exposure to nucleoside reverse transcriptase inhibitors including stavudine (d4T), which is widely used in resource-limited settings. Here we investigated complex pain-related behaviours associated with d4T treatment using ethologically relevant thigmotaxis and burrowing behaviours in adult rats. Detailed neuropathological response was also examined using neurochemistry, electron microscopy, and proteomics. After 2 intravenous injections of d4T (50 mg/kg, 4 days apart), rats developed hind paw mechanical hypersensitivity, which plateaued at 21 days after initial d4T injection, a time that these animals also had significant changes in thigmotaxis and burrowing behaviours when compared to the controls; reductions in hind paw intraepidermal nerve fibre density and CGRP/IB4 immunoreactivity in L5 spinal dorsal horn, suggesting injury to both the peripheral and central terminals of L5 dorsal root ganglion neurons; and increases in myelinated and unmyelinated axon diameters in the sural nerve, suggesting axonal swelling. However, no significant glial and inflammatory cell response to d4T treatment was observed. Sural nerve proteomics at 7 days after initial d4T injection revealed down-regulated proteins associated with mitochondrial function, highlighting distal axons vulnerability to d4T neurotoxicity. In summary, we have reported complex behavioural changes and a distinctive neuropathology in a clinically relevant rat model of d4T-induced sensory neuropathy that is suitable for further pathophysiological investigation and preclinical evaluation of novel analgesics.